2002
DOI: 10.1002/xrs.522
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of metallic ultra‐thin films by grazing‐exit electron probe x‐ray microanalysis

Abstract: Grazing-exit electron probe x-ray microanalysis (GE-EPMA) was used for the quantitative analysis of films with thicknesses of 10 and 4 nm. First-order calibration curves were obtained for the determination of Ti and Cr over a wide range of concentrations. The results confirmed that matrix effects are negligible when the film thickness is below some critical value. The minimum detection limits were obtained at the small exit angles (0. 75 • for the 10 nm thick film on the gold and 0.53 • for the 4 nm thick film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 16 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Substrates with a periodic structure were proposed to enhance the sensitivity. [ 101 ] Furthermore, trace analysis using electron or proton excitation usually showed qualitatively superior background and detection limits in GEXRF conditions as compared to XRF detection at large emission angles [ 45,68,102,103 ] but did not include a thorough quantification. Of course, if analyzing e.g., particles or particle inclusions with electron excitation, it has to be considered that the complexity of the excitation function (the second line in Equation (3), which is rather easily described for X‐ray excitation) can introduce severe uncertainties.…”
Section: Gexrf Applicationsmentioning
confidence: 99%
“…Substrates with a periodic structure were proposed to enhance the sensitivity. [ 101 ] Furthermore, trace analysis using electron or proton excitation usually showed qualitatively superior background and detection limits in GEXRF conditions as compared to XRF detection at large emission angles [ 45,68,102,103 ] but did not include a thorough quantification. Of course, if analyzing e.g., particles or particle inclusions with electron excitation, it has to be considered that the complexity of the excitation function (the second line in Equation (3), which is rather easily described for X‐ray excitation) can introduce severe uncertainties.…”
Section: Gexrf Applicationsmentioning
confidence: 99%
“…Tsuji et al reported new experimental equipment for use in grazing-exit electron probe microanalysis. [123][124][125] This equipment was applied to Pd-Se-Te single particle analysis on a gold substrate and used to establish angle dependent curves for 5 nm thin cobalt film deposited on a silicon wafer. The authors also studied Cr enrichment in polished stainless steel and reported that for a 10 nm Ti or Cr film, detection limits were improved by a factor of 6.5 in comparison with a 45u take-off angle.…”
Section: Related Techniquesmentioning
confidence: 99%